METODE PRACTICE STYLE DAN GUIDED DISCOVERY STYLE SERTA KETERAMPILAN TEKNIK DASAR ATLET BULUTANGKIS - ZULBAHRI ZULBAHRI; CICILIA MELINDA (STKIP ROKANIA, 2019)
This study aims to describe the theory and practice ofthe Method of Practice Style and Guided DiscoveryStyle and the Basic Technical Skills of BadmintonAthletes. The method used is descriptive analysis fromseveral read literature. The conclusions of this articleare: 1) There is the influence of the Practice Stylemethod on the skills of the basic badminton technique,because based on the hypothesis test obtained tcount(8.97) which is greater than t table (1.75). 2). There isthe influence of the Guided Discovery style style methodon the skills of the basic badminton technique becausebased on the hypothesis test obtained tcount (9.06)which is greater than t table (1.75). 3) There aredifferences in the effect of Practice Style with theGuided discovery style style method on the skills of thebasic badminton technique with the mean difference(average) 2.56 with 2.63. Where the Guided Discoverystyle style method is more effective than Practice Stylein improving the skills of basic badminton techniques.